Sistem Informasi Uang Saku Berbasis Web Studi Kasus : Santri Pondok Pesantren Nurul Falah Jabres - Helmi Wahyuriadi; Endang Wahyuningsih (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study aims to design a web-based student pocket money information system at the Nurul Falah Jabres Islamic Boarding School to overcome the problem of managing pocket money which has been done manually. The development method used is waterfall, which consists of the requirements, design, implementation, verification, and maintenance stages. This system is designed using the PHP programming language, MySQL database, and Laravel framework. The results of testing using the black-box method show that all system features, such as login, user management, financial transactions, and announcements, run well and according to their functions. This system is expected to improve the efficiency and transparency of student financial management and facilitate communication between the boarding school and student guardians. This study also recommends developing the system into a mobile version and integrating automatic notifications to improve user convenience.